Evaluation of PMSG (Oodev®) application on hepatosomatic and gonadosomatic index of snakehead fish - Rizal Akbar Hutagalung; Maheno Sri Widodo; Abdul Rahem Faqih (Jurnal Akuakultur Indonesia)
ABSTRACT